Mechanical Characteristics of Ballast Bed under Dynamic Stabilization Operation Based on Discrete Element and Experimental Approaches - Lihua Wang; Zemin Zhao; Jiongli Wang; Xianzeng Li; Yayu Huang; Tingqiang Yao (Shock and Vibration)
To study the mechanical characteristics of ballasted bed under dynamic stability, a three-dimensional discrete element model of ballasted bed with 1000 mm × 700 mm × 550 mm is established based on the discrete element method. Meanwhile, a simulation test bench with the same size is built for simulation analysis and experimental research. The variation law and trend of settlement, lateral resistance, and compactness of ballasted bed under different excitation frequencies are analyzed comprehensively. The results show that when the excitation frequency is constant, the lateral resistance of sleeper, the settlement of sleeper, and the compactness of track bed under sleeper increase first and then tend to be stable. With the increase in horizontal excitation frequency, lateral resistance of ballast bed, sleeper settlement, and compactness first increase and then decrease after stable operation. The values of these parameters are maximized when the excitation frequency is 36 Hz which is the relative optimal horizontal excitation frequency of this model.